2003
DOI: 10.1002/cne.10978
|View full text |Cite
|
Sign up to set email alerts
|

Rostral agranular insular cortex and pain areas of the central nervous system: A tract‐tracing study in the rat

Abstract: The rostral agranular insular cortex (RAIC) has recently been identified as a site where local changes in GABA and dopamine levels, or application of opioids, can alter nociceptive thresholds in awake animals. The connections of the cortex dorsal to the rhinal fissure that includes the RAIC have been examined previously, with emphasis on visceral and gustatory functions but not nociception. Here we examined the afferent and efferent connections of the RAIC with sites implicated in nociceptive processing. Senso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
161
1
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(180 citation statements)
references
References 120 publications
14
161
1
1
Order By: Relevance
“…The connectivity of RAIC suggests that it is involved in multiple aspects of pain behavior, and increasing evidence shows that the RAIC is important for the modulation of nociception in humans and rats. It is suggested that projections to the RAIC from medial thalamic nuclei are associated with motivational/ affective components of pain while RAIC projections to mesolimbic/mesocortical ventral forebrain circuits are likely to participate in the sensorimotor integration of nociceptive processing, and that its brainstem projections are most likely to contribute to descending pain-inhibitory control [44] . Clinical studies have also suggested that the insular cortex is involved in pain modulation.…”
Section: Rostral Agranular Insular Cortex (Raic) Involvement Of the Rmentioning
confidence: 99%
“…The connectivity of RAIC suggests that it is involved in multiple aspects of pain behavior, and increasing evidence shows that the RAIC is important for the modulation of nociception in humans and rats. It is suggested that projections to the RAIC from medial thalamic nuclei are associated with motivational/ affective components of pain while RAIC projections to mesolimbic/mesocortical ventral forebrain circuits are likely to participate in the sensorimotor integration of nociceptive processing, and that its brainstem projections are most likely to contribute to descending pain-inhibitory control [44] . Clinical studies have also suggested that the insular cortex is involved in pain modulation.…”
Section: Rostral Agranular Insular Cortex (Raic) Involvement Of the Rmentioning
confidence: 99%
“…Though the exact mechanism is unknown, IC outputs chronically regulate detection thresholds for painful stimuli in the periphery via GABAergic signais (Jasmin et al, 2003;Jasmin et aL, 2004). In addition, an unusually dense staining region for ~-opioid receptors (primary receptor targets for analgesia-producing opiates such as morphine) is present in the rostral agranular region (Delfs et aL, 1994;Burkey et aL, 1996).…”
Section: Extrahippocampal Involvement In Tle: the Insular Cortexmentioning
confidence: 99%
“…The rostral agranular IC, in particular, is important in regulating peripheral nociceptive thresholds via opioidergic, dopaminergic and GABAergic signaling (Burkey et aL, 1996;Burkey et aL, 1999;Jasmin et al, 2003;Jasmin et aL, 2004). In addition, the rostral agranular IC is reciprocally connected with the perirhinal cortex (PC) (Delatour and Witter, 2002), a structure central in object memory and recognition (Buckley, 2005;Murray et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…It is intensively connected with other cortical and subcortical regions via a cortico-striato-thalamic network (linking the insula also to the caudate nucleus; see Metzger et al 2010), with the lateral hypothalamus (Jasmin et al 2004), the hippocampus [at least with the entorhinal cortex (Mesulam and Mufson 1982)], and the brainstem via corticobulbar pathways (Jasmin et al 2004;Ruggiero et al 1987). We refer for further review of the neuroanatomy and function of the insula to the classical work by Mesulam and Mufson (1985) and an excellent new work by Nieuwenhuys (2012).…”
Section: Abnormal Yawning Due To Insular Lesionsmentioning
confidence: 99%